Development of a referral pathway framework for fetal alcohol spectrum disorder in the Pilbara - James Fitzpatrick; Angela Dudley; Rebecca Pedruzzi; June Councillor; Kaashifah Bruce; Roz Walker (James Cook University, 2020)
Introduction: This article describes the process of mapping referral pathways to develop a localised resource to enhance the journey to diagnosis, treatment and support for fetal alcohol spectrum disorder (FASD) in a regional community setting. Methods: Over a 6-month period, a research officer engaged service providers in Port and South Hedland, Western Australia, using participatory action research methods. An iterative process included a service environment scan, interviews with service leaders and refinement of progressive drafts of the pathway through the Hedland FASD Network. A community reference group advised on cultural issues. Results: Referral pathways for interagency sectors (health, education, justice) were developed. Three pathway schematics and a companion four-page referral protocol were endorsed. The pathways were disseminated to all service providers and consensus was reached to trial the pathways within existing service systems. Conclusion: The process of referral pathway development provided a service mapping and gapping exercise to facilitate service integration. Evaluation of the resource will be conducted using the RE-AIM framework. The referral pathways template has been adapted and trialled by health and other professionals in several sites across Australia. The model developed for FASD can be applied to other neurodevelopmental disorders.